The effectiveness of the combined problem-based learning (PBL) and case-based learning (CBL) teaching method in the clinical practical teaching of thyroid disease - Zhao, Wanjun; He, Linye; Deng, Wenyi; Zhu, Jingqiang; Su, Anping; Zhang, Yong (BMC medical education, 2020)
Background This study aimed to evaluate the effectiveness and efficiency of PBL–CBL combined teaching in thyroid surgery and make observations from the students’ perspectives, based on their satisfaction with the learning process. Methods We prospectively enrolled 354 fourth-year students majoring in clinical medicine, along with 232 residents, from September 2014 to June 2019. These participants were randomly allocated into either the combined PBL–CBL teaching group or the traditional lecture-based classroom group to attend a course about thyroid nodules. Both pre- and post-class quizzes were conducted. An anonymous questionnaire was also administered to both groups to evaluate the students’ perceptions and experiences. We compared the two teaching methods among all the students as well as with the fourth-year students and residents in subgroups. Results The traditional group’s pre-class quiz scores were significantly higher than the PBL–CBL group’s (as determined by a two-tailed t-test at a 95% confidence interval, T = 16.483, P < 0.001). After class, in the PBL–CBL group, the mean total quiz score and the basic knowledge and case analysis scores increased significantly ( P < 0.001). The PBL–CBL group’s performance improvement was significantly higher than the traditional group’s (increasing from 52.76 to 70.51 vs. from 67.03 to 71.97). Furthermore, the scores for learning motivation, understanding, student–teacher interaction, the final examination, communication skills, clinical thinking skills, self-learning skills, teamwork skills, and knowledge absorption, as measured by the survey, were significantly higher in the PBL–CBL group than in the traditional group ( P < 0.001). Meanwhile, the survey scores representing the amount of students’ free time the course consumed were significantly lower in the PBL–CBL group than in the traditional group ( P < 0.001). Conclusions PBL combined with CBL may be an effective method for improving medical students’ and residents’ performance and enhancing their clinical skills.